A 0.1–5.0 GHz SDR transmitter with current-mode power-mixer and self-calibration scheme in 65 nm CMOS. (December 2017) - Yin, Yun; Gao, Yanqiang; Wang, Zhihua; Chi, Baoyong
Abstract: A 0.1–5.0 GHz software-defined radio (SDR) transmitter for private network wireless communication is presented. A V-I converter with the 3rd-order nonlinearity cancellation and current-mode power-mixers are introduced to improve the CIM3 performance. The complete self-calibration scheme is proposed to alleviate the non-ideal effects, including RF resonant frequency self-tuning, LO leakage and image rejection calibration, output power control. With the self-calibration, the transmitter obtains good robustness in RF operation frequency self-tuning and achieves the average LO leakage of −61 dBc and image-rejection ratio (IRR) of 58 dBc. Moreover, the system verifications have demonstrated 24.5 dBm Pout (output power) with 0.7% EVM, 20 dBm Pout with 1.6% EVM, 6.2 dBm Pout with 2.1% EVM for 905 MHz GSM, 905 MHz EDGE and 3.5 GHz LTE signals, respectively. This SDR transmitter has achieved comparable or even better performance in linearity, CIM3 and power consumption compared with the state-of-the-art reconfigurable transmitters.